Jobs Challenges in Slavonia, Croatia – A Subnational Labor Market Assessment - Christiaensen, Luc; Ferre, Celine; Ivica, Rubil; Matkovic, Teo; Sharafudheen, Tara (World Bank, Washington, DC, 2019)
A thriving region until the early 1990s, Slavonia, the eastern region of Croatia, has been confronted with stagnation and decline, ageing and outmigration as well as impoverishment ever since. This followed Croatia's homeland war of 1991-1995, with Slavonia one of the frontlines, economic restructuring of its state-led economy during the 1990s and 2000s and the global economic crisis of the late 2000s. More recently, after Croatia's EU accession in 2013 and coinciding with the economic upswing since 2014 in Croatia and the EU, Slavonia's labor market has started to tighten, with registered vacancies now exceeding the number of job seekers for highly educated as well as some unskilled and semi-skilled occupations. However, inactivity and unemployment remain high. In 2017, the share of the working-age population in work was only 51 percent, 10 percentage points below the rest of Croatia (61 percent) and 17 percentage points below the 2017 EU28 average. A legacy of war, limited availability of care services, and especially lower education levels explain an important part of Slavonia's much higher inactivity and unemployment. On the demand side, labor productivity in Slavonia's firms is systematically lower than in the rest of the country (except in agriculture and forestry), also consistent with Slavonia's sizeablewage gap. This, together with general disenchantment of the Slavonian population with the economicand business environment, has prompted outmigration. At the same time, a small number of firms alsooutperform their sectoral competitors elsewhere in Croatia, signaling Slavonia's potential.Looking ahead, private sector job creation remains a top priority, especially focusing on Slavonia's lower educated, who make up the bulk of the unemployed and inactive. This especially requires a reduction in the regulatory burden and an increase in Slavonian firms' competitiveness, which will also help to close the substantial wage gap with the rest of Croatia. Given the large share of its population in agriculture and forestry-related activities (close to 30 percent), Program Slavonia's current focus on agriculture and forestry is clearly warranted. With Slavonia's longstanding history and labor force experience in manufacturing and the rising number of vacancies in this sector, so is attention to manufacturing.